PELAKSANAAN PENYULUHAN PERTANIAN DI ERA PANDEMI COVID-19 - Haris Tri Wibowo; Diah Sulistyorini (JURNAL SAINS PETERNAKAN NUSANTARA, 2022)
The existence of a global pandemic has changed the order of life in society. The ability to make adaptations and adjustments in the new normal life system is a source of strength that will make us survive. In this regard, the study of the implementation of agricultural extension in the era of the COVID-19 pandemic is relevant and important to study because the success of the adaptation and adjustment process will determine the direction of agricultural development and development in the future. This research uses literature study method. From the study conducted, it was concluded that agricultural extension in the era of the covid-19 pandemic was carried out with change management. With the implementation of change management, adjustment steps are taken as a form of adaptation to existing situations and conditions while still focusing on the goals that have been set. The performance of the instructor in the era of the covid-19 pandemic is determined by the ability of the extension worker to take adaptation steps in an effort to optimize the role of the extension worker in conveying information messages to the target group. The challenges in implementing agricultural extension in the pandemic era are the weak mastery of communication information technology, the inefficient implementation of agricultural extension which is carried out virtually and not many agricultural extension materials related to post-harvest and entrepreneurship as a response to the uncertain situation of the COVID-19 pandemic.Keywords: Agriculture, Extension, Covid-19 Pandemic